Small‐Angle Neutron Scattering and Magnetically Heterogeneous State in Sr2FeMoO6–δ. Issue 5 (19th March 2019) - Kalanda, Nikolay; Garamus, Vasil; Avdeev, Mikhail; Zheludkevich, Mikhail; Yarmolich, Marta; Serdechnova, Maria; Florian Wieland, D. C.; Petrov, Alexander; Zhaludkevich, Aliaksandr; Sobolev, Nikolai
Abstract : Single‐phase strontium ferromolybdate (Sr2 FeMoO6–δ ) samples with different degrees of the superstructural ordering of the Fe/Mo cations ( P ) are obtained from partially reduced SrFeO3–х, SrMoO4 precursors by the solid‐state technology. The study of the temperature dependences of the magnetization measured in the field‐cooling and zero‐field‐cooling modes indicated an inhomogeneous magnetic state of the samples. The presence of magnetic regions of different nature has also been revealed by the small‐angle neutron scattering. For the Sr2 FeMoO6–δ samples with different P values and for all values of the magnetic field induction up to 1.5 T and of the scattering vector in the interval 0.1 > q > 0.002 Å −1, the analytical dependence I ∼ q – α obeys the Porod law ( α ≈ 4), which corresponds to an object with a smooth and well‐marked surface and polydisperse grain size. Deviations from the Porod law in the q > 0.1 Å −1 region and a weakening of the neutron scattering in applied magnetic fields may be ascribed to magnetic inhomogeneities with diameters D < 6 nm, which are partially destroyed/oriented by magnetic fields В ≥ 1.5 T. It is established that the magnetic homogeneity of the Sr2 FeMoO6–δ compound is enhanced with increasing superstructural ordering of the Fe/Mo cations. Abstract : An increase of the Sr2 FeMoO6–δ magnetic moment values can be explained by the presence of antiferromagnetic inclusions confirmed by small‐angle neutron scattering data. Deviations from the Porod law at q > 0.1 А −1 can be ascribed to magnetic inhomogeneities smaller than 6 nm. The magnetic homogeneity of the Sr2 FeMoO6–δ compound is improved with increase of the Fe/Mo cations superstructural ordering.